Octogenarians undergoing cardiac surgery outlive their peers: a case for early referral. Issue 4 (23rd August 2005) - Stoica, S C; Cafferty, F; Kitcat, J; Baskett, R J F; Goddard, M; Sharples, L D; Wells, F C; Nashef, S A M
Abstract : Objective: To examine short and long term outcomes of octogenarians having heart operations and to analyse the interaction between patient and treatment factors. Methods: Multivariate analysis of prospectively collected data and a survival comparison with an age and sex matched national population. The outcomes were base in-hospital mortality, risk stratified by logistic EuroSCORE (European system for cardiac operative risk evaluation), and long term survival. Results: 12 461 consecutive patients (706 over 80 years) operated on between 1996 and 2003 in a regional UK unit were studied. Octogenarians more often had impaired ventricular function, pulmonary hypertension, and valve operations. They also included a higher proportion of women, had a higher serum creatinine concentration, and had a trend towards more unstable angina. Younger patients had a higher prevalence of previous cardiac operation, previous myocardial infarction, and diabetes. The in-hospital mortality rate was 3.9% for all patients (EuroSCORE predicted 6.1%, p < 0.001) and 9.8% for octogenarians (predicted 14.1%, p  =  0.002). Long bypass time and non-elective surgery increased the risk of death above EuroSCORE prediction in both groups. A greater proportion of octogenarians stayed in intensive care more than 24 hours (37% v 23%, p < 0.001). Long term survival was significantly better in the study patients than in a general population with the same age–sex distribution (survival rate at five years 82.1% v 55.9%, p < 0.001). Conclusions: Cardiac surgery in a UK population of octogenarians produced excellent results. Elective referrals should be encouraged in all age groups.